Faktor-Faktor yang Mempengaruhi Implementasi Psak 109 dalam Akuntabilitas Dana Lembaga Amil Zakat (LAZ) - Wiwik Puji Andriani; Diyah Probowulan; Ari Sita Nastiti (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the factors that influence the implementation of the article 109 in the accountability of the Amil Zakat Institution (LAZ) in Jember Regency. This research method is a quantitative method. The type of data used in this study is in the form of responses (responses) given by respondents are written responses, in response to written questions (questionnaires) given by the researcher. The data analysis method used in this research is Multiple Linear Regression Analysis. The results of this study indicated that the Role of Local Government, the Role of Professional Organizations, Management Commitment, Education, and Experience have a positive and significant effect on the implementation of PSAK 109. Conclusion, the Role of Local Government, the Role of Professional Organizations, Commitment of Management, Education, and Experience improve the implementation of PSAK 109. Keywords: Commitment of Management, Education, Experience, Role of Local Government, Role of Professional Organizations